On managing adjustment to external shocks in oil importing developing countries - Sanjeev Gupta; Sübidey Togan (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
This paper employs country specific multisectoral general equilibrium models of Turkey, Kenya and India to study the adjustment problems confronting these countries. The affects of liberal and interventionist policies on GDP and on incomes of different classes are analysed. The results show that liberal policies minimise the GDP losses and that farmers are relatively better off under these policies.
Keywords: 330